Borges and Piranesi - Reinhold Martin (Oz, 1992)
This study is lodged, somewhat awkwardly perhaps, between description and prescription. "Description" is used, in that it aims to represent a particular conceptual relation between Jorge Luis Borges's "Library of Babel" short story, and the final edition, from about 1760, of Giovanni Battista Piranesi's Carceri d'Invenzione series of engravings.